ANTARA TRADISIONALIS DAN MODERNIS: PEMIKIRAN PENDIDIKAN K.H. AHMAD DAHLAN - Kasmuri Selamat (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2019)
The early twentieth century Islamic education was not firmly looking into the aspect of knowledge. What the Islamic world have seen for centuries is the practice of separation between faith, knowledge and intellectualism. In other words, the education system professed a dualism which was without precedence in the Islamic world. Both of the education systems had their own weakness. Under the western education systems the Islamic World practiced a type of education which more emphasized the aspects of intellectualism, which is more towards materialism rather than faith. While the other which is more traditional, developed the aspect of faith and eternity. The Islamic faith suggest its followers to have such belief that if great efforts are made, they will gain bliss and happiness in life and in hereafter. These orientations and basic foundations are also being practiced in the Islamic World. Fulfilling the above aspiration, K.H. Ahmad Dahlan (1923 AD) and his Muhammadiyah organization moved ahead aiming their goals at developing and innovating the education system of Indonesia in particular. He integrated the teaching of Islam and its culture, with the inclusion of the acquisition of knowledge according to the Islamic way.